MEDICO-GEOGRAPHICAL ASSESSMENT ECOLOGICAL-DEPENDENT INCIDENCE OF ADOLESCENT AND CHILD POPULATION OF THE REPUBLIC OF DAGESTAN - A. G. Gasangadzhieva; P. I. Gabibova; M. G. Daudova; S. N Mirzoeva (Юг России: экология, развитие)
Aim. The aim of this research work is to assess the current trends of key indicators of the health of adolescent and child population of the Republic of Dagestan. This study was conducted with the use of modern epidemiologi-statistical methods of analysis of medico-geographical data, therefore, the reliability and the level of expected results is not in doubt. Location. The Republic of Dagestan.Methods. The main methods of the research was currentand retrospective analysis of indicators of regional health mapping method, mathematical and cartographic modeling, methods of medico-geographical analysis. Using mathematical modeling, forecasting and GIS technology built models for further development of medico-ecological systems.Results. A comprehensive health assessment of children and adolescents, allowed us to identify the priority classes of diseases, to carry out territorial differentiation in the level of health, to establish areas with adverse health and geographical setting. The structure of the environmentally sensitive morbidity of children and adolescents in the Republic is dominated by diseases of the respiratory system and the digestive system. As a result of the research showed a clearer distribution of high average annual growth rate of cancer development in children to anthropogenically disturbed urbanized areas (10.9 %). Projected average annual growth rate for infants of rural population will amount to 3.5 %, urban: 4.6 %.Main conclusions. The obtained results can be used in the development of program activities and strategies for socio-economic development, environmental monitoring environment, the health system of the Republic of Dagestan. The results of the studywill help to develop evidence-based recommendations for the prevention of environmental-related diseases relevant to the areas of the Republic of Dagestan, which can be used by institutions of the Ministry of health of the Republic for the screening of the health status of the child population